Elevated glycated haemoglobin is a strong predictor of mortality in patients with left ventricular systolic dysfunction who are not receiving treatment for diabetes mellitus. (22nd September 2015) - John, J; Goode, KM; Rigby, A; Cleland, JGF
Abstract : Background: Glycated haemoglobin (HbA1c) is an indicator of average blood glucose concentrations over the preceding 3 months, is simpler to perform than either a fasting glucose or glucose tolerance test and is associated with a worse prognosis in some clinical settings. However, its relationship with survival in patients with suspected heart failure has not been studied. Methods: Patients referred to a community-based heart failure clinic with suspected heart failure had a comprehensive assessment including the measurement of HbA1c. For this analysis, patients with diabetes mellitus or initiation of diabetic medication in the subsequent 12 months, which might influence HbA1c, were excluded. Findings: Of 970 non-diabetic patients referred between 2001 and 2004, the median age was 72 years (range 25–96 years), 56% were men, 45% had left ventricular ejection fraction (LVEF) ⩽45% and 50% had an HbA1c greater than 6% (upper reference limit). Among patients with LVEF ⩽45% there was an abrupt increase in mortality in those with an HbA1c greater than 6.7% (n  =  68) compared with those with HbA1c ⩽6.7% (n  =  368; hazard ratio (HR) 2.4, p<0.001) and this persisted after adjustment for age and comorbidity (HR 1.9, p = 0.008); respective one year mortalities were 26.5% and 9.4%. This increase in mortality was not seen in those with LVEF greater than 45% (HR 1.44, p = 0.36 after adjustment). Interpretation: The abrupt increase in mortality with HbA1c may make it a useful risk stratification tool in non-diabetic patients with LVEF ⩽45% which could help improve clinical management.